Regression Analysis for the Factor Affecting on Farm Land/Urban Land Value in Urban Sprawl - Zuhal Karakayacı (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the factors affecting on land value in urban sprawl were analysed via regression analysis. In the analyse, the nominal value of land was taken to be dependent variable while factors affecting the value of the land in urban sprawl were considered to be independent variables. 9 factors that were thought to affect the value of the land were handled. In this study, 3 separate models were analyzed, and all models provided statistically significant results. The basic reason for applying three separate models is to be witness the effects by including the variables in different categories (environmental, social amenity and economical factors) separately to the model. As a result of these analyses, all of environmental, amenity and economic factors should be considered for valuation of urban sprawl.